A. E. Rowe & Co., Locks, Knobs, House Trimmings; J. E. Came & Co. Billiard Tables - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of A. E. Rowe & Co., Locks, Knobs, House Trimmings; J. E. Came & Co. Billiard Tables from the 1870 Boston City Directory